Elevated serum platelet count inhibits the effects of brain functional changes on cognitive function in patients with mild cognitive impairment: A resting-state functional magnetic resonance imaging study - Zhang, Yuechan; Liu, Jing; Wei, Zijun; Mei, Jianing; Li, Qianqian; Zhen, Xiaomin; Zhang, Yunyun (Frontiers in Aging Neuroscience, 2023)
Objective: Brain function remodeling has been observed in patients with mild cognitive impairment (MCI) and is closely associated with cognitive performance. However, it is not clear if this relationship is influenced by complete blood counts. This study investigated the role of complete blood counts in the relationship between brain function and cognitive performance. Methods: Twenty-two MCI patients and eighteen controls were enrolled. All subjects underwent resting-state functional magnetic resonance imaging. A neuropsychological battery [Mini-Mental Status Examination, Auditory Verbal Learning Test (AVLT), Symbol Digit Modalities Test, Boston Naming Test (BNT), Shape Trajectory Test B (STT-B), Rey Complex Figure Test (RCFT), Hamilton Anxiety Rating Scale (HAMA), and Hamilton Depression Scale] was used to assess cognitive function, and MCI patients received complete blood counts tests for red blood cells (RBC), white blood cells, hemoglobin (HGB), monocytes, and platelet counts (PLT). Results: Compared with controls, MCI patients demonstrated significantly decreased amplitude of low-frequency fluctuation (ALFF) values in the left dorsolateral superior frontal gyrus, left post orbitofrontal cortex, right medial superior frontal gyrus, right insula, and left triangular inferior gyrus. In the MCI group, there were associations between ALFF values of the left hippocampus (HIP.L) and AVLT (P = 0.003) and AVLT-N5 scores (P = 0.001); ALFF values of the right supramarginal gyrus (SMG.R) and BNT scores (P = 0.044); ALFF values of the right superior temporal gyrus (STG.R) and BNT scores (P = 0.022); ALFF values of the left precuneus (PCUN.L) and STT-B performance (P = 0.012); and ALFF values of the left caudate nucleus (CAU.L) and RCFT-time (P = 0.036). Moreover, the HAMA scores were negatively correlated with RBC and HGB levels, and positively correlated with monocyte count. The PLT count was positively correlated with STT-B performance. Additionally, high PLT count inhibited the effect of ALFF values of the PCUN.L on STT-B performance in MCI patients. Conclusion: ALFF values of the HIP.L, SMG.R, STG.R, PCUN.L, and CAU.L were associated with decreased memory, language, executive function, and visuospatial ability in MCI patients. Notably, elevated PLT count could inhibit the effect of brain functional changes in the PCUN.L on executive function in MCI patients.